3-Indoleacrylic acid from canola straw as a promising antialgal agent - Inhibition effect and mechanism on bloom-forming Prorocentrum donghaiense. (May 2022) - Effiong, Kokoette; Hu, Jing; Xu, Caicai; Zhang, Yiyi; Yu, Shumiao; Tang, Tao; Huang, Yuzhou; Lu, Yongliang; Li, Wei; Zeng, Jiangning; Xiao, Xi
Abstract: Harmful algal blooms (HABs) have induced severe damage worldwide. A novel high-efficient antialgal natural chemical, 3-indoleacrylic acid (3-IDC) with a 5-day half-maximal inhibitory concentration (IC50, 5d ), was discovered from canola straw, and its algal inhibition mechanism was investigated. Adverse effects were observed on the growth of P. donghaiense with 3-IDC addition, following an increase in reactive oxygen species (ROS) production. 3-IDC also hindered the photosynthetic mechanism of P. donghaiense cells. Transcriptional results showed 3-IDC inhibiting the functions of all the nutrient assimilating genes, down-regulated ribulose-1, 5-bisphosphate carboxylase/oxygenase II, and cytochrome f genes. The expression of heat shock protein ( HSP ) 70 and 90 and rhodopsin genes were also suppressed. The binding affinity of investigated receptors was observed. The conformational changes induced by the spatial microstructural alteration through 3-IDC may further contribute to the perturbation of those enzyme catalytic activities. The present results provide new insights on controlling HABs using 3-IDC. Graphic abstract: Unlabelled Image Highlights: 3-IDC is the key allelochemical found in canola straw with an EC50, 5d 0.14 mg/L. 3-IDC increases ROS and distorted algal photosynthesis. 3-IDC reduces mitochondrial membrane potential, and disrupts antioxidant systems. 3-IDC induces the suppression of nutritional, photosynthetic, and defensive genes. 3-IDC breaks electrons conveying proteins via hydrogen bond/hydrophobic interactions.